Experiences of first-time voters with their families during the 2022 presidential elections - Bolante, Joshua Emmanuelle A.; Filamor, Matthew Gabriel R.; Uggadam, Miriam (Quezon City University of the Philippines Diliman, 2024)
Elections are the heart of democratic societies, offering citizens an avenue to influence the government and shape political landscapes. The 2022 presidential elections in the Philippines, held on May 9, marked a significant chapter in the nation’s own democratic journey, characterized by its occurrence in the middle of the COVID-19 pandemic. This study aimed to describe the experiences of first-time voters within their families during the 2022 elections, examining their activities, political discourse, and attitudes to provide insights into their participation and family dynamics. Data from this study were collected through semi-structured, in-depth interviews with fifteen (15) first-time voters living in either Quezon City, Manila City, or Pasay City and must have at least one (1) family member who voted for a different presidential candidate. Through reflexive thematic analysis, themes were established by categorizing them based on the objectives. It was concluded that the experiences of first-time voters during the 2022 presidential elections in the Philippines were significantly shaped by both the COVID-19 pandemic and familial interactions on their political activities and attitudes. Despite the challenges and conflicts encountered, the Filipino family culture of togetherness and mutual respect remains strong, emphasizing the importance of maintaining familial bonds despite differing political views. The findings of this study shall contribute to more election-related studies, as well as being able to identify and understand the experiences of voters and families during these sensitive periods.
In partial fulfillment for the Degree of Bachelor of Science in Family Life and Development
Thesis
Keywords: Elections -- Philippines; Voting -- Philippines; Families -- Political aspects; Political participation -- Philippines